Itinerary of the humanitarian crisis in Syria - Henao-Hidrón, Javier (Universidad Pedagógica y Tecnológica de Colombia, 2014)
Before the emergence of the social and political crisis that prompts these comments, Syria was a country of 21 million inhabitants and 185,180 km2, located in the Near East region, bordering on Turkey, the Mediterranean Sea, Lebanon, Israel, Jordan and Iraq. The so-called Arab spring began in Syria in March 2011 with a protest movement against the dictatorship of the Assad (General Hafiz, the father, ruled with an iron hand for twenty-nine years and Bashar, the son, has been twelve in the same line ). The attitude of the government was even more cruel than in Libya, because it reacted without imposing limits against the rebels and their eventual support within the civilian population, while Russia 1 and China provided support and prevented with their veto that the Security Council of the The United Nations will approve an Arab League plan for a transition to democracy, as well as proposals aimed at pressuring and sanctioning a discredited regime that openly violated human rights.